Transform Learning Through Technology : A Guide to the ISTE Standards for Coaches - Crompton, Helen (Book collections on Project MUSE., 2020)
""The role of the technology coach in education is constantly evolving and encompasses several elements - from establishing relationships with educators to improve learning outcomes to inspiring educators to use technology to ensure access to high-quality learning; from supporting educators to design learning experiences that meet the needs of all students to modeling digital citizenship and supporting educators and students in how to interact in a digital world. This guide to the ISTE Standards for Coaches will help define the role of the coach; show how it relates to the roles addressed in the ISTE Standards for Students, Educators and Education Leaders; share information from research and the learning sciences relating to coaching cycles and methodologies; and present scenarios from coaches in diverse situations and with varied backgrounds"--